2019
DOI: 10.1021/acs.inorgchem.9b02644
|View full text |Cite
|
Sign up to set email alerts
|

Copper2+ Binding to α-Synuclein. Histidine50 Can Form a Ternary Complex with Cu2+ at the N-Terminus but Not a Macrochelate

Abstract: Alpha-synuclein (αSyn) forms amyloid fibrils in the neurons of Parkinson's disease (PD) patients'. Despite a role for Cu 2+ in accelerating αSyn fibril formation, coupled with reports of copper dishomeostasis in Parkinson's disease (PD), there remain controversies surrounding the coordination geometry of Cu 2+ with αSyn. Here we compare visible circular dichroism (CD) spectra of Cu 2+ loaded on to full-length αSyn together with four peptides that model aspects of Cu 2+ binding to the N-terminus and Histidine5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…Consequently, the pathological H50Q mutation has no impact on the kinetics of Cu 2+ binding to the high‐affinity site of αSyn. Such observation is in good agreement with the result obtained by Tian et al ., [23] but contradictory to that of De Ricco and co‐workers [20] . The reason could be that the experimental concentration of αSyn in the latter study was so high that a Cu 2+ bridged ternary complex was generated [23] …”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Consequently, the pathological H50Q mutation has no impact on the kinetics of Cu 2+ binding to the high‐affinity site of αSyn. Such observation is in good agreement with the result obtained by Tian et al ., [23] but contradictory to that of De Ricco and co‐workers [20] . The reason could be that the experimental concentration of αSyn in the latter study was so high that a Cu 2+ bridged ternary complex was generated [23] …”
Section: Resultssupporting
confidence: 80%
“…[20] The reason could be that the experimental concentration of αSyn in the latter study was so high that a Cu 2 + bridged ternary complex was generated. [23] In contrast, using an analogous method, the Cu 2 + binding affinity of NAc-αSyn (K d = 23(3) μM) was determined to be around four orders of magnitude weaker than that of WT-αSyn (K d = 3.0(7) nM). So far, K d values reported for Cu 2 + binding to WT-αSyn as determined by different techniques vary between 0.1 nM and 0.7 μM.…”
Section: Resultsmentioning
confidence: 89%
“…However, it can also involve H50 depending on pH and concentration. 735,736 Copper has been shown to be one of the most potent modulators of αS structure as well as a very effective accelerator of αS fibrillation in vitro. 732 AFM-based experiments revealed that the presence of Cu(II) significantly enhanced the relative abundance of the β-sheet like structure in the otherwise conformationally heterogeneous monomeric αS.…”
Section: α-Synuclein and Metal Ionsmentioning
confidence: 99%
“…In site 1, which has the highest affinity for Cu­(II), the cation is coordinated by the N-terminal NH2 group of M1, the deprotonated backbone amide, the carboxylic groups of D2, and a water molecule. However, it can also involve H50 depending on pH and concentration. , Copper has been shown to be one of the most potent modulators of αS structure as well as a very effective accelerator of αS fibrillation in vitro . AFM-based experiments revealed that the presence of Cu­(II) significantly enhanced the relative abundance of the β-sheetlike structure in the otherwise conformationally heterogeneous monomeric αS .…”
Section: Role Of Metal Ions In Amyloid Diseasesmentioning
confidence: 99%
“…However, if Cu 2? would bind around His50, such an interaction should give rise to a CD signal (Tian et al 2019) and thus we conclude that for our acetylated aSyn variants at our conditions, the affinity of Cu 2? must be less than 100 lM.…”
Section: Discussionmentioning
confidence: 57%